5 - The Ebola Virus Epidemic – What Are the Lessons Africa Can Learn? - Dialo Diop, (CODESRIA Bulletin, 2021)
This article is dedicated to our late sister and comrade, Aminata Diaw Cissé, a philosopher by training, and both a free mind and beautiful spirit of the highest order, an esteemed fighter on all fronts of the African cause, which is none other than the cause of humankind.